Healthcare cost variation in patients with heart failure: a nationwide study. (June 2022) - Bundgaard, J. Skov; Mogensen, U.M.; Christensen, S.; Ploug, U.; Rørth, R.; Ibsen, R.; Kjellberg, J.; Køber, L.
Abstract: Objective: Heart failure (HF) imposes a major economic burden; however, the individual management for patients varies, potentially leading to large cost heterogeneity. The aim of this study was to investigate the spectrum of health cost by patients with HF and factors associated with high direct health cost. Study design: This was a nationwide, retrospective longitudinal study. Methods: Using Danish nationwide registries from 2012 to 2015, we identified all patients aged >18 years with a first-time diagnosis of HF. Total health costs were investigated using two perspectives—at index and during 3 years of follow-up. Patients were investigated by decile cost groups. A multivariable logistic regression was used to identify variables associated with being in the highest cost decile compared with the rest (90%). Results: A total of 11, 170 patients with HF were included, and those in the highest cost decile (n = 1117, 10%) were younger (69 vs. 75 years), fewer were females (34% vs. 43%), and more were inpatients (83% vs. 70%) compared with the rest of the patients with HF (n = 10, 053, 90%). Patients in the highest cost decile (10%) incurred a 30 times higher cost with a mean total health cost in index year of €86, 607 compared with €2893 for patients in lowest cost decile (10%). The results were similar for 3 years aggregated (€139, 473 vs. €4086), corresponding to a 34 times higher cost. Conclusion: In patients with HF, a large total health cost heterogeneity exists with younger age, inpatient admittance, male sex, and comorbidities being associated with a higher likelihood of belonging to the highest cost group.